Brand Personality Model of Chain Drug Stores in Chile - Gallardo-Canales, R; Escobar-Farfan, M (UNIV AUTONOMA CARIBE-UAC, 2018)
This research proposes a brand personality model called "Pharmacy Chains Brand Personality", this industry is relevant, since it is a fundamental pillar for society, as well as for the elaboration of new commercial strategies for consumers. A confirmatory factorial analysis has been applied. The results indicate 14 personality traits grouped into two personality dimensions; transparency and ambition. This document contributes to the brand literature and consumer behaviour, as it delivers consumer behaviour and decision-making patterns in the Chilean pharmaceutical industry.